Wisata Gastronomi Somba Dari Perspektif Peluang dan Tantangan - Mutiara Ulpa (Pringgitan, 2022)
Majene Regency offers diverse tourism potential. One of them is gastronomic tourism which provides opportunities for resource utilization with a culinary orientation from a blend of eating culture and community life. Processed Japanese food, tuing-tuing fish and the smell of peapi which are used as culinary icons and become a tourist attraction in Majene Regency, precisely in Somba, Sendana District are able to provide opportunities as well as answer challenges during the pandemic. The research method used is a qualitative descriptive method with techniques for collecting observational data, library research, interviewing and documentation. The results of the study found that the suitability of the concept was not maximized, the stakeholders were not yet active and the product development strategy had not been carried out.Keywords: Gastronomic Tourism, Opportunities, Challenges, Development